Temporal trends in the management and outcome of obese patients with an acute coronary syndrome – the ACSIS registry 2000–2018. (3rd October 2022) - Gurevitz, C; Mohsen, J; Ovdat, T; Zwas, D R; Fluk Gmach, S; Beigel, R; Eisen, A
Abstract: Introduction: Obesity has been increasing in epidemic proportions over many decades, and is clearly associated with major cardiovascular (CV) risk factors [1–2]. We aimed to examine temporal trends in the management and clinical outcomes of obese patients with an acute coronary syndrome (ACS). Methods: Data from the ACSIS registry including all obese patients (calculated BMI of 30 or above) between the years 2000–2018. Patients were stratified by BMI to obesity classes: Class 1 – BMI 30–34; class 2 – BMI 35–39 and class 3 – BMI 40 and above. Clinical endpoints included 30d MACE and 1-year mortality. Temporal trends were examined in the late (2010–2018) vs. the early period (2000–2008). Results: Among the 13, 816 patients from the ACSIS registry with available BMI data, of whom 3567 were defined as obese, 2670 were in obesity class 1, 679 were in class 2, and 218 were defined as class 3. Patients in higher obesity classes had more CV risk-factors including dyslipidemia, hypertension, and diabetes mellitus (p<0.01 for all interactions). Overall, invasive and pharmacological treatment has improved during time in all obesity classes. The rates of 30-day MACE were numerically higher among patients in class 3 (11.6% in class 1, 11.3% in class 2, and 15.6% in class 3, p-trend= 0.3), and so was the rate of 1-year mortality (7.3%, 7.3%, and 10.9%, respectively, p-trend = 0.1) Comparing the 2 time-periods, 30-day MACE was significantly lower in the late period in class 1 and 2, but has remained unchanged in class 3. Similarly, 1-year mortality has not changed during the years among patients in class 3, but has decreased among patients in classes 1 and 2 (8.6% to 5.8%, p=0.007, and 9.3% to 5.5%, p=0.08, respectively) [Figure 1]. Conclusions: In obese patients admitted with an ACS, the rates of 30-day MACE and 1-year mortality are numerically higher among patients who are extremely obese. During 2 decades, 30-day MACE and 1-year mortality have decreased among obesity classes 1 and 2, but remained unchanged among patients in class 3. Extremely obese patients admitted with an ACS are a particularly high-risk group and future efforts should examine treatment modalities in order to curtail this increased risk. Funding Acknowledgement: Type of funding sources: None.